Hipotensão controlada versus estratégia normotensiva para tratamento do choque hemorrágico em pacientes com aneurisma de aorta abdominal roto. revisão sistemática Cochrane - Moreno, Daniel Hachul [UNIFESP] (2018)
Introduction: An abdominal aortic aneurysm (AAA) is the pathological enlargement of the aorta and can develop in both men and women. Progressive aneurysm enlargement can lead to rupture. The rupture of an AAA is frequently fatal and accounts for the death from haemorrhagic shock of at least 45 people per 100,000 population. The outcome of people with ruptured AAA varies among countries and healthcare systems, with mortality ranging from 53% to 90%. Definitive treatment for ruptured AAA includes open surgery or endovascular repair. The management of haemorrhagic shock is crucial for the person's outcome and aims to restore organ perfusion and systolic blood pressure above 100 mm Hg through immediate and aggressive fluid replacement. This rapid fluid replacement is known as the normotensive resuscitation strategy. However, evidence suggests that infusing large volumes of cold fluid causes dilutional and hypothermic coagulopathy. The association of these factors may exacerbate bleeding, resulting in a 'lethal triad' of hypothermia, acidaemia, and coagulopathy. An alternative to the normotensive resuscitation strategy is the controlled (permissive) hypotension resuscitation strategy, with a target systolic blood pressure of 50 to 100 mm Hg. The principle of controlled or hypotensive resuscitation has been used in some management protocols for endovascular repair of ruptured AAA. It may be beneficial in preventing blood loss by avoiding the clot disruption caused by the rapid increase in systolic blood pressure; avoiding dilution of clotting factors, platelets and fibrinogen; and by avoiding the temperature decrease that inhibits enzyme activity involved in platelet and clotting factor function. Objectives: To compare the effects of controlled (permissive) hypotension resuscitation and normotensive resuscitation strategies for people with ruptured AAA. Search methods: The Cochrane Vascular Information Specialist searched the Specialised Register (April 2016) and the Cochrane Register of Studies (CENTRAL (2016, Issue 3)). Clinical trials databases were searched (April 2016) for details of ongoing or unpublished studies. Selection criteria: We sought all published and unpublished randomised controlled trial (RCTs) that compared controlled hypotension and normotensive resuscitation strategies for the management of shock in patients with ruptured abdominal aortic aneurysms. Data collection and analysis: Two review authors independently assessed identified studies for potential inclusion in the review. We used standard methodological procedures in accordance with the Cochrane Handbook for Systematic Review of Interventions. Main results: We identified no RCTs that met the inclusion criteria. Authors' conclusions: No RCT was found that compared controlled hypotension and normotensive resuscitation strategies in the management of haemorrhagic shock in patients with ruptured abdominal aortic aneurysm that assessed mortality, presence of coagulopathy, intensive care unit length of stay, and the presence of myocardial infarct and renal failure. High quality studies that evaluate the best strategy for managing haemorrhagic shock in ruptured abdominal aortic aneurysms are required.